Comparison of the effect of Acupressure at LI4 and SP6 points on the intensity of Post Cesarean Pain - Tayebeh Negahban Bonabi; Ali Ansari Jaberi; Shayesteh Esmaeilzadeh; Afsaneh Hasanshahi Ravizi (Mashhad University of Medical Sciences, 2018)
Introduction The LI4 and SP6 acupressure points are the most common points to relieve post cesarean pain, but there is no consensus on the preferred point of pressure. Therefore, this study was performed with aim to compare the effect of acupressure at LI4 and SP6 points on the intensity of post cesarean pain. Methods: This double-blind clinical trial study was performed on 90 women referred to the maternity hospitals of Rafsanjan in 2017. They were randomly allocated into three groups: LI4 point, SP6 point and control group. Intervention was performed bilaterally, in 10 seconds of pressure and 2 seconds of rest for 20 minutes sequentially. In the control group, the points were touched with the same pattern without pressure. The intensity of post cesarean pain before, immediately and one hour after intervention was determined by visual analogue Scale in three groups. Data was analyzed by SPSS software (version 16) and ANOVA and repeated measurement variance analysis. P< 0.05 was considered significant. Results: In this study, the mean score of pain at three times of measurement (the time effect) was significant different (p=0.33), but comparison of the mean of three pain score in each group was not significantly different with other groups (p=0.428). The result showed a decrease in pain score trend in the Li4 group during three time  measurements and a decrease in pain score of in the Li4 group compared to the control group in 1 hour after the intervention (p=0.001). Conclusion: The acupressure function at the LI4 point in relieving post cesarean pain is better than the SP6 compression point.